Pembuatan Indeks Artikel Surat Kabar Elektronik Tentang Ekonomi pada Surat Kabar Padang Ekspres dan Kompas Tahun 2015 di Perpustakaan Universitas Dharma Andalas - Putri, Al Ihya Yunus; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2016)
This paper focuses on the manufacture of electronic newspapers indexarticles in Padang Ekspres and Kompasnewspapers 2015 atLibrary of Dharma Andalas University. This paper aims (1) todescribe the process of production of index articles newspaper electronic about economicin Padang Ekspresand Kompasnewspapers years of 2015 at Library of Dharma Andalas University; (2) to describe the result product of index articles electronic newspaper about economic in Padang Ekspres and Kompas newspapers inyears of 2015 atLibrary of Dharma Andalas University.The methods of this paper isdescriptive method with interview and collect data directly from the original source, namely Padang Ekspres and Kompas newspapers at Library of DharmaAndalas University. Based on analyzed the data, it can be summed up as follows: a)the process of production of index articles newspaper electronic about economic in Padang Ekspres and Kompasnewspapers years of 2015 at Library of Dharma Andalas Universitywhich consists of the selection articles about economic in Padang Ekspres and compass Newspapers years of 2015, making description of thw articles, typing the index articles, and scanning of the clipping articles and also compile of indexÂ articles and clipping articles that have been scanned become index articles electronic newspapers ; b) to describe the result product of index articles electronic newspaper about economic in Padang Ekspres and Kompas newspapers inyears of 2015 atLibrary of Dharma Andalas University consisting of a front cover, preface, table of contents, instructions on how to use the index, the index of newspaper articles, the author index, attachment clippings, and back cover. Keywords: indeks; newspaper articles